Pengaruh Gaya Kepemimpinan, Motivasi, dan Kedisiplinan terhadap Kinerja Karyawan PT Intikom Berlian Mustika - Yani Heryanti; Prasetio Ariwibowo; Nicky Rosadi (FOCUS, 2020)
This study aims to determine what factors influence the Leadership Style, Motivation, and Discipline on Employee Performance. The method used in this research is quantitative research methods. The population in this study were all employees of PT Intikom Berlian Mustika in the Operation Support section with a sample of all employees of PT Intikom Berlian Mustika in the Operation Support section, except for a leader. The instrument in this study used an open questionnaire using a Likert scale to measure the attitudes, opinions and perceptions of a person or group of social events or symptoms. The results of this study were partially tested for leadership style variables with a statistical value of 1.585 <2.162, so Ho was accepted, meaning that there was no significant effect of the leadership style variable on employee performance. The partial test results for the motivation variable with a statistical value of 1.376 <2.162, then Ho is accepted, which means that there is no significant effect of the motivation variable on employee performance, so Ho is accepted, which means that there is no significant effect of the motivation variable on employee performance. The partial test results for the discipline variable with a statistical value of 5.969> 2.162, then Ho is rejected, which means that there is a significant effect of the discipline variable on employee performance. Simultaneous test results with a value of 19.288> 2.77, then Ho is rejected, which means that leadership style, motivation, and discipline simultaneously or jointly affect the performance of employees of PT Intikom Berlian Mustika.